Textile machinery and accessories - Rings and travellers for ring spinning and ring twisting frames : - International Organization for Standardization (ISO) (ISO)
This document specifies the principal dimensions of T- and SF-rings, and the mass and tolerance on the mass, of the appropriate travellers for flange rings employed on ring spinning and ring twisting machines. It also specifies the method of designation of the travellers